Motional coherence of fermions immersed in a bose gas - Scelle, Raphael; Rentrop, Tobias; Trautmann, Arno; Schuster, T.; Oberthaler, Markus K. (Physical review letters, 2013)
We prepare a superposition of two motional states by addressing lithium atoms immersed in a Bose-Einstein condensate of sodium with a species-selective potential. The evolution of the superposition state is characterized by the populations of the constituent states as well as their coherence. The latter we extract employing a novel scheme analogous to the spin-echo technique. Comparing the results directly to measurements on freely evolving fermions allows us to isolate the decoherence effects induced by the bath. In our system, the decoherence time is close to the maximal possible value since the decoherence is dominated by population relaxation processes. The measured data are in good agreement with a theoretical model based on Fermi’s golden rule.
Gesehen am 01.02.2022